Guidelines for promoting positive attitudes to preserve Chinese calligraphy among higher education students at Shandong in China - Chun, Jingjian; Ponathong, Chakrit; Bamroongkhan, Pawatwong (International Journal of Innovative Research and Scientific Studies, 2025)
In view of the challenges faced by Shandong University students in the protection of Chinese calligraphy heritage in the digital age, such as the fragmentation of cultural contact and the lag in technology application, this study aims to analyze their protection attitudes and influencing factors and build an intervention framework. To this end, the study uses a mixed research method to carry out a questionnaire survey and semi-structured interviews with 407 calligraphy students from five universities, integrating the theory of cultural identity, the theory of planned behavior, and the knowledge framework of technical teaching content. The results show that students’ recognition of the cultural value of calligraphy is 89%, but only 34% of them actively participate in the protection practice. Their behavioral tendencies are significantly dependent on external incentives such as scholarships, and gender differences and family culture have significant effects. Based on this, the study proposes a three-dimensional intervention framework of "cognitive deepening, emotional cultivation, and behavior guidance," emphasizing the balance between technological empowerment and cultural authenticity, which has practical reference value for optimizing home-school collaboration, improving policy resource allocation, and aligning with the United Nations Sustainable Development Goals (SDG 11.4).